2022
DOI: 10.3758/s13414-022-02538-8
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic landing positions reveal that eye movements are affected by distractor-based retrieval

Abstract: Binding theories assume that stimulus and response features are integrated into short-lasting episodes and that upon repetition of any feature the whole episode is retrieved, thereby affecting performance. Such binding theories are nowadays the standard explanation for a wide range of action control tasks and aim to explain all simple actions, without making assumptions of effector specificity. Yet, it is unclear if eye movements are affected by integration and retrieval in the same way as manual responses. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…In general, the absence of binding effects as proposed by action control theories has been discussed as being incongruent with theoretical assumptions made by binding approaches in action control (Hilchey et al, 2018; Huffman et al, 2018; Schöpper & Frings, 2022, 2023; Schöpper et al, 2020); yet, this pattern has been observed in attentional orienting paradigms investigating IOR multiple times (e.g., Kwak & Egeth, 1992; Taylor & Donnelly, 2002; see Huffman et al, 2018). Interestingly and congruent with action control theories, IOR can be masked by binding effects (Hilchey et al, 2018; Schöpper et al, 2022b; see also Schöpper & Frings, 2022) or response repetition heuristics (Christie & Klein, 2001; Klein, 2004), if the response is discriminatory toward sequentially presented stimuli (e.g., Taylor & Donnelly, 2002; Terry et al, 1994); this observation shares striking similarities with the observation that a discriminatory judgment can lead to binding effects (Huffman et al, 2018; Schöpper et al, 2020).…”
Section: Current Studymentioning
confidence: 68%
See 2 more Smart Citations
“…In general, the absence of binding effects as proposed by action control theories has been discussed as being incongruent with theoretical assumptions made by binding approaches in action control (Hilchey et al, 2018; Huffman et al, 2018; Schöpper & Frings, 2022, 2023; Schöpper et al, 2020); yet, this pattern has been observed in attentional orienting paradigms investigating IOR multiple times (e.g., Kwak & Egeth, 1992; Taylor & Donnelly, 2002; see Huffman et al, 2018). Interestingly and congruent with action control theories, IOR can be masked by binding effects (Hilchey et al, 2018; Schöpper et al, 2022b; see also Schöpper & Frings, 2022) or response repetition heuristics (Christie & Klein, 2001; Klein, 2004), if the response is discriminatory toward sequentially presented stimuli (e.g., Taylor & Donnelly, 2002; Terry et al, 1994); this observation shares striking similarities with the observation that a discriminatory judgment can lead to binding effects (Huffman et al, 2018; Schöpper et al, 2020).…”
Section: Current Studymentioning
confidence: 68%
“…On one side, one might muse that overall response speed might have led to this pattern: Responses became faster from Experiments 1 to 3, while the effects became smaller from Experiments 1 to 3. Retrieval-based effects take time to emerge (Frings & Moeller, 2012; Schöpper et al, 2022a, 2022b); accordingly, retrieval in Experiment 1 might have had the most time to unfold. This is supported by larger IOR in Experiment 1 compared to Experiments 2 and 3, as IOR takes time to emerge as well (e.g., Chao et al, 2020; Panis & Schmidt, 2022; Schöpper & Frings, 2023; Taylor & Ivanoff, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments 1 and 2 suggested that slow responses do not lead to retrieval in detection and localization performance. To gain more support for this, we looked at cumulative reaction time distributions based on reaction time percentiles (e.g., Schöpper & Frings, 2022 , 2023 ; Schöpper et al, 2022a , b ; Taylor & Ivanoff, 2005 ). As binding in detection performance can manifest in a main effect with a benefit of (nonspatial) feature repetition (see Schöpper & Frings, 2023 ; Schöpper et al, 2020 ), we not only looked at the interaction of color and location, but also at the calculated main effects of color and location.…”
Section: Methodsmentioning
confidence: 99%
“…Several ideas have been proposed why S-R binding effects are regularly absent in detection (and localization) performance. First, it has been argued that a discriminatory component is what leads to the observation of S-R binding effects (e.g., Schöpper et al, 2020 , 2022a , b )—if it is absent, binding effects are not observed. This fits well with different outcomes for detection and discrimination procedures in visual search (e.g., Krummenacher et al, 2009 ; Müller & Krummenacher, 2006 ; for a discussion, see Schöpper et al, 2020 ), highlighting the importance of a discrimination response for observing partial repetition costs in search displays (Zehetleitner et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%